Poly-ADP ribose polymerase (PARP) inhibitor regimens for platinum-sensitive ovarian cancer in randomized, double-blind, phase III controlled trials: protocol for a systematic review and network meta-analysis - Peng, Xiaolian; Liu, Jie (Frontiers in Medicine, 2025)
IntroductionClinical trials have shown that PARP inhibitors are effective in treating patients with platinum-sensitive ovarian cancer. They have been indicated to improve progression-free survival or overall survival in patients with patients with platinum-sensitive ovarian cancer. However, there is insufficient comprehensive evidence regarding the comparison of different agents. To evaluate and compare the efficacy and side effects of various PARP inhibitors.MethodsWe plan to conduct a network meta-analysis that includes randomized, double-blind, controlled phase III trials of Niraparib, Rucaparib, Olaparib, or Veliparib in patients with Platinum-sensitive ovarian cancer. The primary outcomes will be progression-free survival or overall survival. The secondary outcome will be grade ≥ 3 of treatment-emergent adverse events. Published and unpublished studies will be retrieved through PubMed, Embase, the Cochrane Library, ClinicalTrials.gov, and the World Health Organization (WHO) International Clinical Trials Registry Platform from 1990 to 2023. We will use STATA V.14.0 to perform all analyses, and the RevMan software to report the risk of bias in the included studies. We will determine the quality of evidence using the GRADEpro GDT software online version. This is a protocol description only. Results and conclusions are subject to completion. This study will be based on published studies, since no primary data collection will be carried out, no formal ethical assessment is required. The network graph and meta-analysis will be used to compare all PARP inhibitors. Their ranking will employ a rankogram, surface under the cumulative ranking curves, and mean ranks.DiscussionOur study will answer the most important question in platinum-sensitive ovarian cancer: which PARPi should be preferred regarding efficacy and side effects? Trials of platinum-resistant or refractory ovarian cancer will be excluded. The limitation is that the results of network meta-analyses do not yet have the same level of evidence as direct head-to-head trials. However, it is a useful complementary method when direct comparative studies cannot be performed. We plan to publish the results of this systematic review and network meta-analysis in peer-reviewed scientific journals, conferences, and the mass media.Systematic review registrationPROSPERO, CRD42024511248, available from: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024511248.